The role of human herpesvirus (HHV) infections and persistent immune activation in antiretroviral therapy-treated HIV infected individuals / Yap Siew Hwei - Yap, Siew Hwei (2018)
Co-infections with human herpesvirus (HHV) have been associated with residual chronic inflammation in antiretroviral therapy (ART)-treated human immunodeficiency virus (HIV)-infected individuals. However, the burden of HHV co-infection among HIVinfected individuals is unknown in the developing country and the role of HHV in modulating the kynurenine pathway and clinical outcomes in HIV-infected individuals is poorly understood. Thus, we investigated (1) the seroprevalence of and the risk factors associated with four common HHVs among treated HIV-infected individuals, (2) the association of HHV with kynurenine/tryptophan (K/T) ratio and (3) other chronic immune activation markers and the impact of HHV infection on long-term CD4 T-cell recovery in HIV/HHV co-infected individuals. In this cross-sectional study, HIV-infected patients receiving suppressive ART for a minimum of 12 months were recruited from the University Malaya Medical Centre (UMMC), Malaysia. Stored plasma was analyzed for CMV, VZV, HSV-1 and HSV-2 IgG antibody levels, immune activation markers (interleukin-6, interferon-γ, neopterin), kynurenine and tryptophan concentrations. The influence of the number of HHV co-infection and K/T ratio on CD4 T-cell recovery was assessed using multivariate Poisson regression. A total of 232 HIV-infected individuals was recruited and all participants were seropositive for at least one HHV; 96.1% with CMV, 86.6% with VZV, 70.7% with HSV-1 and 53.9% with HSV-2. Multivariate analysis revealed that a longer duration on ART was associated with an increased odd of both HSV-1 (aOR: 1.12; 95% CI: 1.02-1.22) and HSV-2 (aOR: 1.12; 95% CI: 1.04-1.21) infection. HSV-2 seropositivity was also associated with being female (aOR: 3.03; 95% CI: 1.31-7.0) and with a history of AIDS defining illness (aOR: 2.01; 95% CI: 1.12- 3.60). Indian ethnicity was associated with a lower odds of CMV (aOR: 0.17; 95% CI: 0.04- iv 0.80) and VZV (aOR: 0.26; 95% CI: 0.09-0.71)seropositivity compared to ethnic Chinese. In addition, higher current CD4:CD8 ratio was also significantly associated with lower odds of CMV seropositivity (aOR: 0.21; 95% CI: 0.07-0.68). K/T ratio was significantly positively correlated with antibodies for CMV (rho=0.205, p=0.002), VZV (rho=0.173, p=0.009) and a tendency with HSV-2 (rho=0.120, p=0.070); with CMV antibody titers demonstrating the strongest modulating effect on K/T ratio among the four HHVs. In multivariate analysis, higher K/T ratio (p=0.03) and increasing number of HHV coinfections (p<0.001) were independently associated with poorer CD4 T-cell recovery following 12 months of ART initiation. These data suggested that co-infection with multiple HHV are common among ART-treated HIV-infected participants in the developing country setting and are associated with persistent immune activation and poorer CD4 T-cell recovery.